KENDALA DAN UPAYA PENGEMBANGAN OBJEK WISATA BONO DI SUNGAI KAMPAR KECAMATAN TELUK MERANTI KABUPATEN PELALAWAN RIAU (JURNAL SPASIAL, 2016)
Bono attractions Teluk Meranti in the Kampar river has long been known by the local community and society outside the area.. The potential development of one of the tourist destinations of special interest is very great because not only the arrival of world-class surfers are also attracted families join surfers to enjoy the beauty of Teluk Meranti village that has not been untouched by modernization. The study aimed to collect data and analyze data on: 1) The potential attraction owned by Bono. 2) Constraints faced in the development of attractions Bono. 3) The efforts made by the government and the community in the development of attractions Bono. This type of research is qualitative using interviews, observation and research directly spaciousness. The results of research in the field as follows: 1) The potential attraction that Bono Bono has become Icon in provincial and national. 2) Constraints faced in the development of attractions Bono among others: Street who has not been on the tarmac, villa or venue that is still inadequate, stalls where to eat the tourists are still lacking, there is no public transportation to transport tourists. 3) The efforts made by the government and the community in the development of attractions Bono is to prepare themselves in order to promote activities pariwisatai does not eliminate their cultural identity. Keywords: Constraints and Development Efforts Attractions Bono